Transmigrasi Masyarakat Hindu Bali di Seputih Raman Lampung Tengah - Nurlaili, Lutvi Dwi (TAMADDUN: Jurnal Ilmu Sosial, Seni, dan Humaniora, 2024)
This study aims to explain the transmigration process of the Balinese Hindu community in Seputuh Raman, Central Lampung. This study uses a descriptive narrative method where the data is explained narratively without conducting in-depth analysis. Lampung Province is one of the provinces in Indonesia that is a destination for transmigration. It is also a province founded by various tribes, one of which is the Balinese community. Transmigration is an effort to develop a region that has been implemented since the era of regional autonomy, to develop new areas and reduce poverty. However, in the era of regional autonomy, transmigration must be adjusted to the characteristics and specific conditions of the region. The transmigration program is said to be successful because of the findings that mention the success of the Balinese community in building a life in Lampung since they first arrived in Lampung.